Answer:
y = -2/3x + 3
Explanation:
First, we need to calculate the slope of the line. We can do this by using the slope formula using two points:
(y₂ - y₁) / (x₂ - x₁)
If we take the points (-3,5) and (3,1), then: y₂ = 1; y₁ = 5; x₂ = 3; x₁ = -3
Next, we can substitute in values in the equation above to get (1 -5)/(3+3)
** We got 3+3 because it was 3 - (-3), where two negatives equal a positive**
Then, we get, -4/6, which simplifies to -2/3. Our slope is -2/3
After that, we need to find the y-intercept, which is where the line intercepts the y-axis. Here, that is at (0,3).
Therefore, if we put the above information into slope-intercept form:
y = mx + b --> m = -2/3; b = 3
y = -2/3x + 3
Though I don't think that answer choice is there...